2010
DOI: 10.1007/s11104-010-0306-5
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminolevulinic acid improves photosynthetic gas exchange capacity and ion uptake under salinity stress in oilseed rape (Brassica napus L.)

Abstract: Salinity is one of the major constraints in oilseed rape (Brassica napus L.) production. One of the means to overcome this constraint is the use of plant growth regulators to induce plant tolerance. To study the plant response to salinity in combination with a growth regulator, 5-aminolevulinic acid (ALA), oilseed rape plants were grown hydroponically in greenhouse conditions under three levels of salinity (0, 100, and 200 mM NaCl) and foliar application of ALA (30 mg/l). Salinity depressed the growth of shoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
88
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(104 citation statements)
references
References 50 publications
15
88
1
Order By: Relevance
“…1' plants. The same results have been observed in oilseed rape (Naeem et al, 2010). Previous research has also demonstrated the ability to improve g s and E of watermelon and pakchoi plants under different conditions by exogenous ALA treatment (Sun et al, 2009;Memon et al, 2009).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…1' plants. The same results have been observed in oilseed rape (Naeem et al, 2010). Previous research has also demonstrated the ability to improve g s and E of watermelon and pakchoi plants under different conditions by exogenous ALA treatment (Sun et al, 2009;Memon et al, 2009).…”
Section: Discussionsupporting
confidence: 81%
“…Watanabe et al (2000) evaluated12 different PGRs and found ALA to be the most effective in improving the salt tolerance of cotton. Thus far, research conducted on ALA has mainly focused on photosynthesis (Liu et al, 2013), chlorophyll accumulation (Memon et al, 2009), the antioxidant system (Nishihara et al, 2003;Sun et al, 2009), and ion uptake (Naeem et al, 2010). Although ALA has been reported to be capable of enhancing the salt tolerance of various plants, data on the molecular mechanism of exogenous ALA application are limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NaCl tolerance is enhanced by increasing the osmolyte content and the physiological activity of protective enzyme systems in plants (Al-Qurashi et al, 2011). Exogenous ALA can improve protective enzyme activity and leaf photosynthesis in various crops, such as Cucumis sativus L. (Zhen et al, 2012), Solanum lycopersicum , Helianthus annuus L. (Akram et al, 2012), Brassica campestris L. (Naeem et al, 2010), Brassica rapa L. (Wang et al, 2005), Solanum tuberosum (Zhang et al, 2006), Oryza sativa L. (Nunkaew et al, 2014), and Creeping bentgrass (Yang et al, 2014), under salinity stress. As a result, the development and production of crops are facilitated, in addition, the inhibitory actions of salinity stress on plants are alleviated.…”
Section: Introductionmentioning
confidence: 99%
“…Application of low concentration of exogenous ALA is known to promote plant growth development and response to environment stresses (Naeem et al, 2012), for example, enhancing salt tolerance in potato (Zhang et al, 2006) and chilling tolerance in pepper seedlings (Korkmaz et al, 2010). Foliar application of ALA can also improve leaf water relations in oilseed rape (Naeem et al, 2010). Na + concentration of cotton seedlings under salt stress were suppressed to low concentrations with ALA (Watanabe et al, 2000a).…”
Section: Introductionmentioning
confidence: 99%